Tumor Suppressor 4.1N/EPB41L1 is Epigenetic Silenced by Promoter Methylation and MiR-454-3p in NSCLC - Yang, Qin; Zhu, Lin; Ye, Mao; Zhang, Bin; Zhan, Peihe; Li, Hui; Zou, Wen; Liu, Jing (Frontiers in Genetics, 2022)
Non-small-cell lung cancer (NSCLC) is divided into three major histological types, including lung adenocarcinoma (LUAD), lung squamous cell carcinoma (LUSC) and large-cell lung carcinoma (LCLC). We previously identified that 4.1N/EPB41L1 acts as a tumor suppressor and is reduced in NSCLC patients. In current study, we explored the underlying epigenetic mechanisms of the 4.1N/EPB41L1 reduction in NSCLC. 4.1N/EPB41L1 gene promoter region was highly methylated in LUAD and LUSC patients. LUAD patients with higher methylation level in the 4.1N/EPB41L1 gene promoter (TSS1500, cg13399773 or TSS200, cg20993403) had a shorter overall survival time (Log-rank p=0.02 HR=1.509 or Log-rank p=0.016 HR=1.509), whereas LUSC patients with higher methylation level in the 4.1N/EPB41L1 gene promoter (TSS1500 cg13399773, TSS1500 cg07030373 or TSS200 cg20993403) had a longer overall survival time (Log-rank p=0.045 HR=0.5709, Log-rank p=0.018 HR=0.68 or Log-rank p=0.014 HR=0.639 respectively). High methylation of the 4.1N/EPB41L1 gene promoter appeared to be a relatively early event in LUAD and LUSC. DNA methyltransferase inhibitor 5-Aza-2’-deoxycytidine restored the 4.1N/EPB41L1 expression at both the mRNA and protein levels. MiR-454-3p was abnormally high-expressed in NSCLC and directly targeted 4.1N/EPB41L1 mRNA. MiR-454-3p expression was significantly correlated with 4.1N/EPB41L1 expression in NSCLC patients (r=-0.63, p<0.0001). Therefore, we concluded that promoter hyper-methylation of the 4.1N/EPB41L1 gene and abnormally high-expressed miR-454-3p work at different regulation levels but in concert to restrict 4.1N/EPB41L1 expression in NSCLC. Taken together, this work contributes to elucidate the underlying epigenetic disruptions of 4.1N/EPB41L1 deficiency in NSCLC.